Molecular Characterization of Ferulate 5-Hydroxylase Gene from Kenaf (Hibiscus cannabinus L.) - Jonggeun Kim; Bosung Choi; Young-Hwan Park; Byoung-Kwan Cho; Hyoun-Sub Lim; Savithiry Natarajan; Sang-Un Park; Hanhong Bae (The Scientific World Journal)
The purpose of this study is to clone and characterize the expression pattern of a F5H gene encoding ferulate 5-hydroxylase in the phenylpropanoid pathway from kenaf (Hibiscus cannabinus L.). Kenaf is a fast-growing dicotyledonous plant valued for its biomass. F5H, a cytochrome P450-dependent monooxygenase (CYP84), is a key enzyme for syringyl lignin biosynthesis. The full length of the F5H ortholog was cloned and characterized. The full-length F5H ortholog consists of a 1,557-bp open reading frame (ORF) encoding 518 amino acids (GenBank Accession number JX524278). The deduced amino acid sequence showed that kenaf F5H had the highest similarity (78%) with that of Populus trichocarpa. Transcriptional analysis of F5H ortholog was conducted using quantitative real-time PCR during the developmental stages of various tissues and in response to various abiotic stresses. The highest transcript level of the F5H ortholog was observed in immature flower tissues and in early stage (6 week-old) of stem tissues, with a certain level of expression in all tissues tested. The highest transcript level of F5H ortholog was observed at the late time points after treatments with NaCl (48 h), wounding (24 h), cold (24 h), abscisic acid (24 h), and methyl jasmonate (24 h).